Comminuted middle third orbito-zygomatic complex fracture leading to blindness due to unanticipated tyre rim explosion during service - A rare case - R Sathyanarayanan; K Raghu; M Shyamala; Jude B Nithin Joseph; R Rajkumar (Wolters Kluwer Medknow Publications, 2021)
An explosion is caused by conversion of solid, liquid into gas with resultant energy release. Blast injuries of large tyres are similar to injuries resulting from landmine explosions. Most of the patients were polytraumatised, initial evaluation and management should follow ATLS. Trauma following tyre blast results in severe soft tissue, orthopedic and head injuries. Head and face is the most commonly affected region followed by upper limb. A 40 year old male patient was watching a car tyre getting inflated with air. Unfortunately the tyre rim exploded on his face, which led to penetrating injury to the eye ball and comminuted middle third fractures. Patient was stabilized and primary hemostasis was achieved. Fractured maxilla was fixed by arch bar wiring and stabilized by using circum-suspension wiring bilaterally. Left eyeball was removed due to open globe injury and intraocular content loss. Unusual maxillofacial injuries are more common. Decision making and treatment of facial penetrating injuries depends on number of factors, which includes location and extent of injury, type of foreign body involved, proximity of vital structures, extent of injury to soft and hard tissue and the relative benefits and risk ratio for the patient. In this case report we have explained about the primary assessment and management of blast injuries.